2017
DOI: 10.1111/jns.12199
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of diet‐induced mechanical allodynia by metabolic parameters and inflammation

Abstract: Dietary-associated diseases have increased tremendously in our current population, yet key molecular changes associated with high-fat diets that cause clinical prediabetes, obesity, hyperglycemia, and peripheral neuropathy remain unclear. This study examines molecular and metabolic aspects altered by voluntary exercise and a high-fat diet in the mouse dorsal root ganglion. Mice were examined for changes in mRNA and proteins encoding anti-inflammatory mediators, metabolic-associated molecules, and pain associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
7
18
0
Order By: Relevance
“…After exercise treatment at 10 weeks of age, body weight of the exercised db/db mice (42.875 ± 1.102 g, n = 4 mice) was similar to that of non-exercised db/db mice (46.15 ± 1.341 g, n = 4 mice; p = 0.1624, two-way ANOVA followed by Tukey’s). This is consistent with previous studies that showed beneficial effects of exercise on diabetes and its complications without body weight changes, including improved glycemic control and albuminuria (Somineni et al, 2014 ), reduced allodynia (Cooper et al, 2017 ), increased hippocampal dendritic spine density (Stranahan et al, 2009 ), and prevention of type 2 diabetes in patients with impaired glucose tolerance (Pan et al, 1997 ). Together, these data demonstrate that exercise treatment attenuated hyperglycemia, providing the appropriate experimental approach to test if the development of type 2 diabetes changes AIS morphology.…”
Section: Resultssupporting
confidence: 91%
“…After exercise treatment at 10 weeks of age, body weight of the exercised db/db mice (42.875 ± 1.102 g, n = 4 mice) was similar to that of non-exercised db/db mice (46.15 ± 1.341 g, n = 4 mice; p = 0.1624, two-way ANOVA followed by Tukey’s). This is consistent with previous studies that showed beneficial effects of exercise on diabetes and its complications without body weight changes, including improved glycemic control and albuminuria (Somineni et al, 2014 ), reduced allodynia (Cooper et al, 2017 ), increased hippocampal dendritic spine density (Stranahan et al, 2009 ), and prevention of type 2 diabetes in patients with impaired glucose tolerance (Pan et al, 1997 ). Together, these data demonstrate that exercise treatment attenuated hyperglycemia, providing the appropriate experimental approach to test if the development of type 2 diabetes changes AIS morphology.…”
Section: Resultssupporting
confidence: 91%
“…This is similar to what was found in a different study using this AID, in which the AIDinduced prevention of mechanical and thermal sensitivity in a model of inflammatory pain did not prevent increases body weight and adiposity (28). Additionally, an exercise intervention reversed high fat diet-induced mechanical allodynia and had no effect on body weight or glucose tolerance (53). There is a positive association between pain and body mass index (62) that is often assumed to be causally related.…”
Section: Discussionsupporting
confidence: 85%
“…The high fat (35%) NAID elevated perigenital withdrawal thresholds in NMS male, but not female, mice which is similar to the increase in hindpaw allodynia that was previously found in males on 54% high fat diet (53). The anti-inflammatory components in the AID prevented this high fat diet-induced hypersensitivity, independent of body weight.…”
Section: Discussionsupporting
confidence: 78%
“…However, other tissue specific sources of proinflammatory cytokines could also mediate tissue-specific MetS complications. In parallel to our study, Cooper and colleagues demonstrated the upregulation of TNF-α, IL-1β and IL-6 in DRG of HF mice during the period of pain behaviors [ 63 ]. Our results suggest that neurogenic proinflammatory cytokines released from the epidermal small nerve fibers could be important mediators for the skin inflammatory phenomena that contribute to the development of pain behaviors in MetSPN.…”
Section: Discussionsupporting
confidence: 80%